The Combined Impact of the Flipped Classroom, Collaborative Learning, on Students’ Learning of key Marketing Concepts - Motameni, Reza (Journal of University Teaching and Learning Practice, 2018)
Purpose of the Study: The overall purpose of this study was to investigate whether or not the incorporation of combined flipped classroom, and collaborative learning pedagogical schemes in two restructured sections of principles of marketing course, had any positive impact on students’ learning of 100 key marketing concepts, processes, and strategies. Results: By comparing the students’ total assessment scores in Experimental and Control Group groups, it was concluded that the re-structured course had significantly improved students’ learning of key marketing concepts, processes, and strategies.